Industrial design protection in the european community and Turkey - Okan, Nimet Ebru (My University, 1999)
Endüstriyel tasarım hukuku, fikri mülkiyet hukukunun bir alt dalıdır. Bu çalışmada, endüstriyel tasarımların uluslararası hukuktaki yeri ve Türkiye ve Avrupa Topluluğu'ndaki endüstriyel tasarım koruma sistemlerinin karşılaştırması yer almaktadır. Uluslararası hukukta endüstriyel tasarımlar 1883 tarihli Paris Sözleşmesi, 1886 tarihli Bern Sözleşmesi, 1925 tarihli Lahey Anlaşması, 1968 tarihli Locarno Anlaşması ve 1996 tarihli TRIPS Anlaşması ile korunmaktadır. Türkiye'de ise endüstriyel tasarımlar 5846 Sayılı Fikir ve Sanat Eserleri Kanunu ve 554 Sayılı Endüstriyel Tasarımların Korunması Hakkında Kanun Hükmünde Kararname ile korunmaktadır. 554 sayılı KHK endüstriyel tasarımlara beş yıllık süreyle yirmi beş yıla kadar uzatılabilen tescilli koruma sağlarken, 5846 Sayılı Kanunla sağlanan koruma yetmiş yıl sürelidir ve tescilsizdir. Avrupa Topluluğu'nda endüstriyel tasarımlar 98/ 71/ EC No'lu Yönerge ile korunmaktadır. 554 sayılı Türk Endüstriyel Tasarım Kararnamesi ile AT'nin Yönergesi arasında büyük ölçüde benzerlik vardır. Ancak koruma şartları açısından iki metin arasında bazı farklılıklar vardır; Türk hukukunda koruma için gereken kriterler daha yüksektir. Diğer önemli bir farklılık ise yarı-iletkenlerin topografyalarının Türk Endüstriyel Tasarım Hukukunda korunmadığı halde AT Endüstriyel Tasarım Hukukunda korunmasıdır. Yine önemli bir farklılık bileşik bir ürüne bağlı yedek parçalar ile ilgilidir. 98/ 71/ EC No'lu AT Yönergesinde, üye devletler arasında , bu konuyla ilgili tam bir uzlaşmaya varılamamıştır. AT, bu konuda nihai bir sonuca vardığında Türk hukukunda da, AT ile tam bir uyum sağlayabilmek için gerekli değişikliklerin yapılması gerekecektir.

Industrial design law is a sub-field of intellectual property law. In this study industrial design law in international law is examined and a comparison of the industrial design law of Turkey and the European Community is made. In international law industrial designs are protected through the Paris Convention of 1883, the Berne Convention of 1886, the Hague Agreement of 1925, the Locarno Agreement of 1968 and the TRIPS Agreement of 1996. In Turkey industrial designs are protected through both the Law on Intellectual and Artistic Works, No: 5846 and the Decree Law No: 554 on the Protection of Industrial Designs. The Decree Law provides registered protection to industrial designs and the term of protection is five years which can be extended up to twenty-five years. The protection granted by Law No: 5846 is unregistered and lasts for seventy years. In the EC industrial designs are protected through the Directive 98/ 71/ EC. The Turkish Decree Law No: 554 and Directive 98/ 71/ EC are nearly identical. There are some differences between the two texts in the protection requirements criteria; the threshold for protection is higher in Turkish law. Another important difference is that topographies of semi-conductors are not granted protection under the Turkish industrial design law; whereas in EC law they are. Besides there are some important differences among the two texts in the field of the use of component parts for the repair of complex products. In the EC a full-scale approximation on this issue could not be introduced in Directive 98/ 71/ EC. When a compromise is established in the EC on this issue, Tukey will have to make the necessary arrangements in its industrial design law in order to reach full compliance with the EC.
Keywords: AVRUPA TOPLULUĞU